Two fossil thrips from Ethiopian amber (Thysanoptera) with description of Merothrips aithiopicus sp. n. (Thysanoptera: Merothripidae) - Ulitzka, Manfred R. (Zootaxa, 2020)
Amber has rarely been found in Africa and only a few samples with fossil inclusions are known (Kiefert et al. 2015). The most important fossiliferous find was reported from an outcrop at the north-western Plateau of Ethiopia a decade ago, revealing diverse inclusions of arthropods, plant remains, fungi and microorganisms (Schmidt et al. 2010). Initially, this amber was classified as originating from the mid-Cretaceous. Later studies, however, have raised questions about this determination and indicated a much younger age: Cenozoic, likely Miocene (Coty et al. 2016, Perrichot et al. 2016, Perrichot et al. 2018). The contradictory—and rather controversial discussed—new dating was based on spectroscopic analyses, revised palynological data and more comprehensive palaeoentomological results showing that insect fossils mostly belong to extant families and genera. In total, Schmidt et al. (2010) reported 22 insects from eight identified orders including two specimens of Thysanoptera: “an undetermined, wingless thrips“ (obviously a larva) and a female associated with Merothripidae. A more detailed analysis of these specimens is the objective of the present study; regarding the larva, only a rough classification and description is given, as fossil larvae cannot be definitely associated with adult specimens.